PEK BUNG KESENIAN TRADISIONAL DI PANDAK BANTUL - Noor Sulistya Budi (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2019)
Pek Bung is a traditional music ensemble in Pandak District under Bantul Regency. Pek is the sound of bamboo produced by hitting it with a beater and bung a membranophone, a one-sided membrane drum made of klenthing (a pottery water jar) whose mouth is covered by a membrane made of a piece of inner tube. The sound bung is produced by striking the drum head. Pek Bung is also a multi-timbre ensemble consisting of both traditional and modern instruments, such as klenthing drum, bass bamboo (wind instrument), kenthongan (bamboo chime), maracas, wood guiro shaker, triangle, keyboard, gambang (bamboo xylophone), flute, and ukelele. Using primary and secondary data, this descriptive research looks at the form of Pek Bung ensemble, its function, the values embedded in the ensemble. The results showed that the performance of Pek Bung ensemble is divided into three parts: opening, content, and closing. The songs are presented in keroncong style, campursari and sholawat or qosidah. Pek Bung ensemble has several functions, such as religious message, entertainment, communication, education, preservation of symbols. Pek Bung ensemble contains several values, such as religious, social and cultural values.